2015
DOI: 10.3390/su7055705
|View full text |Cite
|
Sign up to set email alerts
|

Energy Savings Potential for Pumping Water in District Heating Stations

Abstract: Abstract:In district heating stations, the heat carrier is circulated between the energy source and consumers by a pumping system. Fluid handling systems, such as pumping systems, are responsible for a significant portion of the total electrical energy use. Significant opportunities exist to reduce pumping energy through smart design, retrofitting, and operating practices. Most existing systems requiring flow control make use of bypass lines, throttling valves or pump speed adjustments. The most efficient of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…1,2 As a type of energy storage material, phase change materials (PCMs) can store or release energy during the phase change process, and it is an important and highly efficient method for saving energy. 3,4 Typically, PCMs can be assigned into inorganic, inorganic-organic composite and organic phase change materials on the basis of their chemical compositions. 3,5 Organic PCMs have been used widely because of their numerous merits, including self-seeding nucleation behavior, favorable thermal and chemical stability, suitable melting temperature range, low cost, and temperate transformation enthalpies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 As a type of energy storage material, phase change materials (PCMs) can store or release energy during the phase change process, and it is an important and highly efficient method for saving energy. 3,4 Typically, PCMs can be assigned into inorganic, inorganic-organic composite and organic phase change materials on the basis of their chemical compositions. 3,5 Organic PCMs have been used widely because of their numerous merits, including self-seeding nucleation behavior, favorable thermal and chemical stability, suitable melting temperature range, low cost, and temperate transformation enthalpies.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Typically, PCMs can be assigned into inorganic, inorganic-organic composite and organic phase change materials on the basis of their chemical compositions. 3,5 Organic PCMs have been used widely because of their numerous merits, including self-seeding nucleation behavior, favorable thermal and chemical stability, suitable melting temperature range, low cost, and temperate transformation enthalpies. [6][7][8] Fatty acids, as one of the numerous organic PCMs, have become a current research hotspot because of their outstanding characteristics, including high heat capacity, suitable range of melting temperature, high surface tension, available and congruent melting, slight volume variation, low degree of supercooling and low commodity cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the larger cost elements is pumping energy and may overshadow a pump's life cycle costs, especially when the pumps work for more than 2000 h per year. There is a big potential for electricity consumption reduction can be made which through a proper selection and design of pumping systems and controls [2]. Motor speed can be changed by numerous methods for examples eddy current coupling or hydraulic, variable pulley and gear box system but most efficient method is by change the supply voltage and frequency to the motor [3].…”
Section: Introductionmentioning
confidence: 99%
“…The study also find that fiscal policies are necessary to incent industrial heating saving energy. Ioan et al [7] estimated energy conservation potential of heating stations and provided a set of reasonable suggestions to minimize the environmental impact of heating stations. Barkenbus [8] compared different income groups in America and found that the lower-income group set the thermostat higher in heating season than other income groups.…”
Section: Literature Reviewmentioning
confidence: 99%